Comparative research of the Wild Sage (Salvia nemorosa L.) population and selected clones flowering biology - Kapirnyák, Tünde; Koroknai, Judit; Kováts†, Zoltán; Fári, Miklós (Acta Agraria Debreceniensis, 2013)
The collected and evaluated of morphological Salvia variants widespread application provides for a new type of hungaricum series create. The excellent drought and frost tolerant Salvia nemorosa L. is climate change-tolerant perennials include. At the right time carried out with the new propagation cutting method can be shortened the seedling time, because in 1 year from broke cuttings develops flowering population. The flowering period of Salvia during one vegetation period may extended with right fertilization and phytotechnical, so it becomes suitable for planting in public spaces.